Effects of Stone Removal via Different Approaches in the Treatment of Incarcerated Upper Ureteral Calculi: A Comparative Study - Xiaoliang Yuan; Hanping Wei; Xiaowu Liu; Zhimin Jiao; Tingchun Wu; Honglei Shi (Emergency Medicine International)
Objective. The aim of this study is to investigate the clinical effects of percutaneous nephrolithotomy and transurethral ureteroscopic lithotripsy in the treatment of incarcerated upper ureteral calculi. Methods. This study retrospectively reviewed 400 patients with incarcerated upper ureteral calculi admitted to the hospital from January 2016 to December 2021. Among them, 200 patients treated with percutaneous nephrolithotomy were included in the percutaneous group and 200 patients treated with transurethral ureteroscopic lithotripsy were included in the transurethral group. Perioperative indicators and stone clearance rates on day 7 and 1 month after operation and the reoperation rate were compared between the two groups. The incidence of postoperative complications was recorded. Results. The operation time and postoperative hospital stay of the percutaneous group were longer than those of the transurethral group (P<0.05). There was no significant difference in intraoperative blood loss, 24 h postoperative pain score, stone clearance rates on day 3 and day 14 after operation, or the reoperation rate between the two groups (P>0.05). Postoperative complications in the two groups were mainly grade I and II. The total incidence of complications in the percutaneous group was significantly lower than that in the transurethral group (P<0.05). Conclusion. Both percutaneous nephrolithotomy and transurethral ureteroscopic lithotripsy are effective in the treatment of incarcerated upper ureteral calculi. The former can reduce the incidence of postoperative complications, but the operation time and postoperative hospital stay are longer.